1982
DOI: 10.1002/1097-0142(19820715)50:2<236::aid-cncr2820500213>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Thallium-201-chloride thyroid scintigraphy to evaluate benign and/or malignant nodules usefulness of the delayed scan

Abstract: The purpose of this study is to evaluate benign and/or malignant thyroid tumors with 201TI thyroid scan. We studied 76 cases of histologically verified thyroid tumors, all seen as cold nodules on the 123I thyroid scan. 201TI thyroid scan was performed 5–15 minutes (early scan) and 3–5 hours (delayed scan) after intrayenous administration of 1.5–2.0 mCi of 201TI. In 35 (94.6%) of 37 malignant tumors (anaplastic carcinoma, six; papillary carcinoma, 23; follicullar carcinoma, five; epidermoid carcinoma, one; mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…(Ochi et al, 1982;Tonami et al, 1989;El-desouki 1991). show accumulation of 201TI on both the early and the delayed scans.…”
Section: |mentioning
confidence: 99%
“…(Ochi et al, 1982;Tonami et al, 1989;El-desouki 1991). show accumulation of 201TI on both the early and the delayed scans.…”
Section: |mentioning
confidence: 99%
“…Thallium-201 (/°iT1) has been shown to accumulate similarly to gallium-67 citrate (Winchell 1976) in a variety of benign and malignant tumours (Hisada et al 1978;Ochi et al 1982). The mechanism of the initial extraction of 2°lT1 by the neoplastic tissue seems not to be a completely flow-dependent process.…”
Section: Discussionmentioning
confidence: 99%
“…Though this isotope is reported to be highly sensitive in the diagnosis of differentiated carcinoma, 29 it has a low ability to distinguish between malignant and benign lesions. Ochi et al 30 introduced the technique of early and delayed scanning in order to enhance the diagnostic accuracy of thallium 201 scanning. They reported that this technique has increased the specificity of the method to 90% without a decrease in sensitivity (95%).…”
Section: Other Uses For the 99m Tc Scanmentioning
confidence: 99%